1998
DOI: 10.1159/000014064
|View full text |Cite
|
Sign up to set email alerts
|

Gut Regulatory Peptide Levels in Bovine Fetuses and Their Dams between the 3rd and 9th Months of Gestation

Abstract: Several gut regulatory peptides were measured by radioimmunoassay between 3 and 9 months of gestation in the plasma of 91 bovine fetuses and their dams, in fetal gastric content and in amniotic fluid. During gestation, plasma peptide concentrations did not change in cows. Likewise, fetal plasma concentrations of cholecystokinin, somatostatin, secretin and vasoactive intestinal polypeptide showed no variation while those of gastrin, pancreatic polypeptide and gastric inhibitory polypeptide increased during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Moreover, plasma levels of gut regulatory peptides seem to be independent of maternal levels and are high at the end of gestation [45,106]. Therefore, the ontogenesis of GI and pancreatic endocrine cells (gastrin, cholecystokinin (CCK), pancreatic polypeptide (PP), somatostatin) in porcine fetuses [57] and the high concentrations of gut regulatory peptides during gestational age in bovine fetuses [45] [75]. Since PP is considered to reflect the vagal input [ 112], it may also reflect a pro-trophic effect of vagal nerves on digestive tract tissue.…”
Section: Effect Of Age On Digestive Productions and Enzyme Expressionsmentioning
confidence: 99%
“…Moreover, plasma levels of gut regulatory peptides seem to be independent of maternal levels and are high at the end of gestation [45,106]. Therefore, the ontogenesis of GI and pancreatic endocrine cells (gastrin, cholecystokinin (CCK), pancreatic polypeptide (PP), somatostatin) in porcine fetuses [57] and the high concentrations of gut regulatory peptides during gestational age in bovine fetuses [45] [75]. Since PP is considered to reflect the vagal input [ 112], it may also reflect a pro-trophic effect of vagal nerves on digestive tract tissue.…”
Section: Effect Of Age On Digestive Productions and Enzyme Expressionsmentioning
confidence: 99%
“…Evidence that regulatory peptides in the animal fetus are released has only been shown for gastrin, PP and GIP (26,27). The differences in frequency of co-localization of the various polypeptides at different fetal ages suggest that they have a regulatory role also in human.…”
Section: Journal Of Endocrinology (1999) 141mentioning
confidence: 99%
“…To our knowledge, the gut regulatory peptide concentrations in amniotic fluid, digestive content, placental and/or maternal and foetal plasma were measured during the last third of gestation in ovine and bovine species and only one study concerning a long period (between 3 and 9 months) is available in bovine species (Guilloteau et al, 1998a). Taking together these works, it can be concluded that in the ruminant foetus: 1. the concentrations of gut regulatory peptides in plasma are independent from those measured in their dams, suggesting that independent synthesis and secretion occur in the foetus, 2. due to the chemical conditions in the gut lumen, the gut regulatory peptides are stable in this milieu and their major source in the amniotic fluid is the enteral circulation of the fluid swallowed by the foetus, thus draining the luminal peptide contents caudally, 3. gastrointestinal endocrine cells appear to be regulated, as shown by the decrease of plasma gastrin and pancreatic polypeptide (PP) concentrations upon somatostatin infusion in sheep foetus (Shulkes and Hardy, 1982), 4. the endocrine system for some peptides is functional as early the 3 rd month of gestation, and finally, 5. these diverse observations suggest that foetal endocrine cells release their secretory granules in a regulated manner, and that the peptides are capable of interfering with functional targets.…”
Section: Foetal Periodmentioning
confidence: 99%
“…The mitotic Figure 1. Evolution with age of plasma concentrations of six gut regulatory peptides (pmol/L) and abomasum, pancreatic and small intestinal weights relative to the body weight (%) in bovine foetuses and preruminant (♦◊) and ruminant (■) calves (adapted from Toofanian et al, 1974;Le Huërou-Luron et al, 1992;Toullec et al, 1992;Guilloteau et al, 1984aGuilloteau et al, , 1992bGuilloteau et al, , 1998a Days GUILLOTEAU P., ZABIELSKI R. index in the crypts was lower and the size of "lysosomal vacuoles" (a marker of gut mucosal maturity) as well as the percentage of vacuolated enterocytes in the jejunum and ileum were higher after treatment with a CCK 1 receptor antagonist (Biernat et al, 1999). Interestingly, similar results were obtained in neonatal pigs suggesting that endogenous CCK may be an universal regulator of gut mucosa maturation (Biernat, 2002).…”
Section: Neonatal Periodmentioning
confidence: 99%
See 1 more Smart Citation